Exploring Knowledge from the Qur'an: The Concept of Multidisciplinary Education in Islamic Culture - Fitria Puji Atma Dewi; Hani' Ni'matul Ula; Eva Kumalasari (JISEI: Journal of Islamic Studies and Educational Innovation, 2025)
The concept of multidisciplinary education in Islamic culture is rooted in the teachings of the Qur'an which emphasizes the balance between religious knowledge and worldly knowledge. In the history of Islamic civilization, this approach has produced scientists who have mastered various fields of science, such as Ibn Sina, Al-Farabi, and Al-Kindi. This article explores the concept of multidisciplinary education from the perspective of the Qur'an and how it is applied in classical Islamic culture and its relevance in the world of modern education. With a qualitative approach based on literature studies, this study examines the verses of the Qur'an that support the integration of science and an analysis of the practice of Islamic education in history. The results of the study show that multidisciplinary education in Islam is not only relevant to building an advanced civilization, but is also able to answer the challenges of the times while adhering to Islamic values.